Vibration characteristics of fiber reinforced self compacting mortars (FRSCM) - Kumar, P. Rathish; Srikanth, K.; Rao, M.V. Krishna; Oshima, Toshiyuki (Journal of Structural Engineering, 2025)
Monitoring the changes in the response parameters of a structure has been a widely accepted method for the assessment of structural integrity, performance and safety. The problem of concreting in portions of congested reinforcement has being solved with the intervention of Self Compacting Concretes and Mortars. In the present work, the mechanical and vibration characteristics of Self Compacting Mortars covering the parameters such as aggregate type, type of fiber and the mesh type has been investigated. It was noticed that there is a marginal increase in the compressive strength and split tensile strength with fiber additions and using complete natural aggregate. The flexural strength performance was better in GI wire based specimens. The natural aggregate based Self Compacting showed higher natural frequencies. It was also noted in general that with the increase in damage level, there was a decrease in the frequency. The resonant frequencies have increased with Glass Fiber additions and reinforcement.